Citrus pulp and orange fiber as dietary fiber sources for dogs - Pacheco, Peterson Dante Gavasso [UNESP]; Baller, Mayara Aline [UNESP]; Peres, Francine Mendes [UNESP]; Ribeiro, Érico de Mello [UNESP]; Putarov, Thaila Cristina [UNESP]; Carciofi, Aulus Cavalieri [UNESP] (Elsevier, 2021)
Citrus pulp pellets (CPP) and orange fiber (OF) are coproducts of the citrus juice industry. OF is a novel fiber source that contains elevated amounts of soluble fiber and has not yet been studied in dog nutrition. The objectives of this study were to evaluate the inclusion of CPP and OF in dog foods and their effects on the extrusion parameters, the coefficient of total tract apparent digestibility (CTTAD) of nutrients, fermentation end products, and palatability. A control diet (CO) without an added fiber source tested was formulated, and the experimental diets were composed of 30 g/kg, 60 g/kg and 120 g/kg CPP or 60 g/kg OF inclusion (as-fed basis). Extrusion parameters were recorded to determine extruder energy balance and kibble macrostructure. Thirty beagle dogs (3.2 ± 0.7 years; 12.4 ± 1.5 kg body weight) were distributed in a randomized block design with 6 dogs per group to evaluate the CTTAD of nutrients and the fermentation products in feces. The results were analyzed by analysis of variance, and means were compared by polynomial and orthogonal contrasts. The inclusion of CPP and OF reduced motor amperage (P < 0.001), mass pressure (P = 0.002), and specific mechanical energy transference (P < 0.001). Kibble macrostructure was affected by a decrease in expansion and an increase in hardness by CPP and OF inclusions (P < 0.001). Starch gelatinization was reduced by CPP (P < 0.001) but not by OF inclusion (P > 0.05). Total dietary fiber (TDF) intake increased (P < 0.001) with the addition of CPP, with a linear reduction in CTTAD of nutrients and energy (P < 0.05). The OF treatment, however, presented similar CTTAD values of DM and CP to those of the CO diet (P > 0.05). The TDF CTTAD was higher for 60 g/kg OF than for 60 g/kg CPP (P = 0.028). The fecal pH decreased, and total short-chain fatty acids (SCFA), acetic acid, butyric acid, and lactate concentrations increased with CPP and OF inclusion (P < 0.05). However, the diet supplemented with OF induced the production of feces with a lower pH and higher total SCFA concentrations than those of feces produced from CPP inclusion (P < 0.001). The OF diet presented a higher preference (65%) than the CO diet (35%) by dogs (P < 0.05). The CPP and OF were fermentable fiber sources, increasing SCFA and butyric acid concentrations in feces. The OF was more fermentable than CPP, with a limited impact on kibble formation, starch cooking, and CTTAD of nutrients and showing good acceptance on diets by dogs.
Keywords: Butyric acid; Digestibility; Extrusion; Fermentation products; Palatability; Soluble fiber